2018
DOI: 10.3126/ajms.v9i4.19725
|View full text |Cite
|
Sign up to set email alerts
|

A hospital based plain radiographic observational study of lumbosacral transitional vertebrae in the Nepalese population

Abstract: Background: Presence of lumbosacral transitional vertebra may lead to number of clinical consequences because of failure to correctly number the problematic vertebra and also has been associated with low back pain. Different studies done at different part of the world have shown wide range of prevalence of lumbosacral transitional vertebra.Aims and Objective: This hospital based cross sectional observational study was undertaken to determine the prevalence of lumbosacral transitional vertebra among the Nepales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
2
5
2
Order By: Relevance
“…In this study, LSTV was found in 61 (17.8%) subjects out of 343 pa ents. Similar to this finding, the prevalence of LSTV in various studies has been reported to 1,6,[8][9][10][11][12][13][14][15][16][17] be about 10% to 20%.…”
Section: Discussionsupporting
confidence: 81%
“…In this study, LSTV was found in 61 (17.8%) subjects out of 343 pa ents. Similar to this finding, the prevalence of LSTV in various studies has been reported to 1,6,[8][9][10][11][12][13][14][15][16][17] be about 10% to 20%.…”
Section: Discussionsupporting
confidence: 81%
“…Sacralization was more common than lumbarization, similar to other studies. 1,6,9 A study conducted in Australia reported lumbarization to be more common than sacralization, in contrast to our study, which could be because of the exclusion of type I LSTV in his study causing decreased recorded cases of sacralization. 8 LSTV was more common in females in our study which was similar to other studies conducted in a similar setting in Nepal.…”
Section: Discussioncontrasting
confidence: 90%
“…The prevalence rate reported in our study was 9.48%, which was lower compared to similar studies conducted in Nepal. 1,6 However, in an MRI-based study, 7 the LSTV prevalence was 3.8%, much lower as compared to our study. Similarly, other similar studies from India and Saudi Arabia had lower prevalence as compared to this study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…[31][32][33][34][35][36][37]. Olofin MU et al observed the highest incidence of TV (37%) in Nigerian population[12].The knowledge of occurrence of TV is of utmost important for clinicians as it may be associated with increased risk of disc degeneration, disc herniation and stenosis of spinal canal and neural foramina[17].CONCLUSIONSacrum is highly variable bone exhibiting variations such as skewness, AAS, SB and TV.…”
mentioning
confidence: 99%